Flouting Maxims in Creating Humor: A Comparison Study Between Indonesian and American - Maulidya Ayu Puspasari; Lisetyo Ariyanti (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2019)
In a stand up comedy, the Stand-up comedian or also known as comic have to tell about their restlessness to the audience in a funny way. In order to make the audience laugh, they surely need to make the audience understand the topic being discussed. Concerning to the success of a communication, Paul Grice (19890 proposed four cooperative principles that people expected to follow; maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner (Yule, 1996). However, Attardo claims that disobeying maxims is common in a research of humor (Attardo, 1990). Thus, this study is purposed to compare the flout of maxims done by an Indonesian comic and an American comic, its joke techniques which they employ while flouting maxims to create humorous materials and the reason why they flout certain maxim the most and use certain joke techniques. This study uses descriptive qualitative method to observe the result of flouting maxims in Stand up comedy. The result finding of this study will be in a form of descriptive text. The participants of this study are an Indonesian comic named Abdur Arsyad and an American comic named Kevin Hart. The result of this study finds that the maxims each comics flout the most are different which is influenced by the difference of their nationalities and cultures. Kevin flouts maxim of quantity the most because of the influence of American culture which tend to be direct in communication. Meanwhile, Abdur flouts maxim of quality the most because of the influence of Indonesian culture which tend to be indirect in communication. Even though the maxim they flout the most are different, their flout of maxims are similarly employed all types of joke techniques which contributed to create humor. Their flouts of maxims have employed paralanguage, ridicule, satire, and politeness strategy of joke techniques. The similarity of the joke techniques employed by both comics is influenced by their ethnic background. Abdur Arsyad and Kevin Hart have different nationalities, however they have the same ethnic background. Abdur comes from East side of Indonesia, and Kevin is African-American which both are minority in their countries. Therefore, they employ the same joke telling technique to deliver the jokes. It can also be influenced by their joke materials which are similar. Both of them usually bring up the topic of the restlessness of being minority and about social criticism.